(untitled) (Revista Española de Fisiología, 1973)
Oxygen uptake and galactose and water transfer by everted sacs of intestine of the fish Gobius paganellus have been measured at 25, 30 and 37° C. The O5 uptake increased with temperature, but it became stabilized between 30 and 37° C. The water transfer from mucosal to intestinal wall increased with temperature. A linear correlation between O- uptake and water transfer to tissue has been observed. The water transfer from mucosal to serosal decreased with temperature rises and became nil at 37° C. The active transport of galactose increased with the temperature reaching a maximum at 30° C, and started to diminish at 37° C. The absence of Na+ in the incubation medium inhibited O2uptake, and water transfer to tissues and to serosal side. The galactose active transport was very strongly inhibited by the absence of Na+.